PERKULIAHAN FISIKA DASAR BERBASIS MASALAH DIDUKUNG MULTIMEDIA INTERAKTIF DENGAN PLATFORM ANDROID UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS, KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN ICT - Ma'ruf, - (2022)
This research is motivated by the low ability of students in critical thinking, problem solving and ICT abilities. This study aims to develop problem-based basic physics lectures supported interactive multimedia with android platform (PBL-MMIa) to improve students' critical thinking skills, problem solving and ICT abilities. The research method used is the method (Research and Development, R & D) which refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were students who programmed the Basic Physics course for the 2021-2022 academic year in the physics education study program at one of the LPTK in South Sulawesi. Subjects in the experimental class as the treatment class used PBL-MMIa as many as 17 students and the control class as a comparison class using PBL without interactive multimedia support as many as 17 students. The research instrument consisted of essay tests of critical thinking skills, problem solving and ICT abilities. The results of the study have succeeded in developing a problem-based basic physics lecture design supported interactive multimedia with android platform (PBL-MMIa Models) with the characteristics of having a syntax consisting of five phases, and each phase there are independent learning activities with interactive multimedia on the android platform. The five phases are as follows: (1) Student orientation to problems; (2) Organizing students to study; (3) Independent and group investigations; (4) Develop and display Artifacts and presentations, (5) Analyze and evaluate problem solving processes on 5 lecture materials/topics related to basic physics. The test results show that the PBL-MMIa lecture model is more able to improve critical thinking skills, problem solving abilities and ICT abilities than the ordinary PBL model as indicated by the acquisition of a normalized gain score and mann whitney test results.